Advanced thermal response tests: A review. (March 2020) - Wilke, Sascha; Menberg, Kathrin; Steger, Hagen; Blum, Philipp
Abstract: In this study, the historical and technical development and the current status of distributed (DTRT) and enhanced (ETRT) thermal response tests (TRT) are reviewed. The different test setups of these advanced TRT are critically assessed and future research questions are outlined. Advanced TRT use specific temperature measurement techniques for the depth-resolved determination of site-specific ground parameters that are required for an optimal design of borehole heat exchanger (BHE) fields. The depth-resolved determination of these thermal properties, such as effective thermal conductivities and thermal borehole resistances, is the key advantage in comparison to conventional TRT, promising economic benefits during the installation and operating phase of ground source heat pump (GSHP) systems. Various test setups exist which differ regarding the heating procedure, i.e. circulating heating fluid and heating wire, the temperature measurement technique, i.e. optical fiber and wireless probe, as well as in their suitability for parameter estimation. These advanced techniques can furthermore provide information about geological layers, fractured zones and groundwater influenced sections in the subsurface as well as inadequate backfilled zones along the borehole heat exchanger. Despite this, advanced TRT are reported in international literature only for a few locations and some test setups are purely theoretical without any practical demonstration. Uncertainties exist regarding the comparability of the test setups, the sensitivity of the measurement devices under test conditions, as well as the best evaluation procedure. Also, scarce information is available about the use beyond academic field and economic aspects in comparison to conventional TRT. Encouraging further research and a more extensive transfer of these promising techniques from academia to practice is therefore also the aim of this review. Highlights: Advanced TRT enable the depth-resolved determination of ground thermal parameters. The temperature measurement is conducted either by optical fibers or wireless probes. Different test setups exist for advanced TRT, with individual (dis)advantages. Open questions exist regarding the best test setup and the utilization in practice.